Continuous coronary sinus and arterial pH monitoring during pacing-induced ischaemia in coronary artery disease. - Cobbe, S M (1982)
Catheter tip pH electrodes were used for continuous recording of coronary sinus and arterial pH during atrial pacing in 20 patients undergoing coronary arteriography for chest pain. An ischaemic response to atrial pacing was identified by the onset of angina and/or electrocardiographic abnormalities. Technically satisfactory coronary sinus recordings were obtained in 18 patients. Mean coronary sinus pH at the peak pacing rate fell by 0.021 +/- 0.006 units (n = 9) in the ischaemic group, while there was no significant change in the non-ischaemic group. A larger fall in coronary sinus pH (-0.052 +/- 0.009) was found in the ischaemic group in the 30 seconds after the end of atrial pacing, the maximum change occurring after 16.1 +/- 1.5 seconds. A maximum fall of coronary sinus pH greater then 0.02 units identified patients with an ischaemic response. Changes in arterial pH did not account for these results. The sensitivity of coronary sinus pH recording for the detection of ischaemic heart disease is enhanced by sampling during the "washout" phase after the end of pacing.